(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study examines self-regulated learning (SRL) with an emphasis on the ways in which students’ underlying motives impact motivational regulation techniques. Through the integration of theoretical frameworks related to motivation and self-regulation, we investigate the range of tactics students use to control their motivation and how these strategies change depending on their motivational orientation. Insights into the dynamic interaction between motivation and self-regulation in educational environments can be gained from a thorough evaluation of the literature, which identifies important variables influencing the application of motivational regulation techniques. Our results highlight how crucial it is to comprehend how each person’s motivational regulation differs in order to facilitate efficient learning strategies.